A cracking shot! depressed skull fracture sustained from a golf ball in a 16-year old. (3rd September 2017) - McGuinness, Rachel B.; Jalloh, Ibrahim; Macarthur, Donald C.
Abstract: Depressed skull fractures sustained from golf balls are quite rare. We report such a case in a 16-year old, and demonstrate its appearance in a 3D CT reconstruction.